RESORT AREA WITH REGIONALISM ARCHITECTURAL APPROACH AND THERMAL COMFORT IN KLEDUNG TEMANGGUNG - Aldhi Nugroho; Hermawan Hermawan; Adinda Hendriani (Clean Energy and Smart Technology, 2023)
The design of this Resort area uses the Thermal Comfort Approach. Using suitable materials and contemporary concepts, buildings in this area will later become comfortable lodgings and increase new comfort for new tourists. The realization of the conceptual basis for planning and designing a Resort in Kledung Temanggung, which is equipped with supporting facilities that can provide a sense of comfort through interior and exterior spatial processing based on the Regionalism Architecture Approach and Thermal Comfort, which can attract tourists. The methodology to be used in the design and planning of the Resort at Kledung Temanggung is competitively descriptive, and the data collection method obtained both primary and secondary data. This article produces a design concept for planning and designing a resort area by considering the existing thermal in the Temanggung district.